Pemberdayaan Kelompok Usaha Perhutanan Sosial (KUPS) Perikanan Desa Sekabuk Melalui Budidaya Ikan Nila (Oreochromis niloticus) - Putra, Yudha Perdana; Mudlofar, Farid (Kapuas, 2024)
Sekabuk Village is located in Mempawah Regency of Kalimantan Barat Province which has social forestry areas managed by local community, proven by lawfully legal certificate. In vicinity of those social forestry areas lies river that host various endemic species and also area of ponds owned by community that are hugely potential to be developed for fish farming business, one of which is nile tilapia (Oreochromis niloticus). PPM activities purposes are to implement available technological inovation to build and develop independent economy of the community through transfer of aquaculture technology, especially nile tilapia farming in earthen ponds. Furthermore provide assistance in the process of farming until harvesting period. Also to financially analyze the feasibility of nile tilapia farming business continuation in Sekabuk Village. PPM activities were conducted for 5 months, from June through October 2023. The activities stages were survey, initial discussion with stakeholders, infrastructure preparation, aquaculture science and technological counseling, fry stocking, fish rearing with assistance until harvesting, marketing the product, and analyzing financially the feasibility of business continuation. As many as 2000 nile tilapia fry were stocked in the earthen pond and then rared for 4 months. The yields were 1630 fish (81,5%) where as many as 1050 fish have average weight of 200 gram each, with selling price at Rp. 25.000/kg to collectors and 210 kg of total production, and 580 fish with average weight of 150 gram each, with selling price at Rp. 20.000/kg to local community and 87 kg of total production. The financial analysis shows that the R/C value of the business amounted to 1,3 which indicate that the business continuation of nile tilapia farming in earthen pond is feasible.